GROWTH AND YIELD QUALITY OF SWEET CORN, AS INFLUENCED BY NITROGEN FERTILIZATION LEVELS IN SULAIMANI REGION - A. A. Mohammed,; Z. M. Majid,; S. A. S.Kasnazany,; S. J. Salih, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Four sweet corn varieties (Zea mays ssp. Saccharata), Gold Rush (v1) and Chocolate (v2), originated from Japan and 001(v3), and 003 (V4) are France originated, were cultivated under the effect of three different levels of nitrogen fertilization (120, 170and 230 ) kg ha-1as (N1, N2, and N3) in two different locations in Sulaimani region (Bakrajo and Kanipanka), Iraqi Kurdistan Region in order to investigate the effects of some environmental and climatic factors on growth performance and yield quality of sweet corn varieties in the open field. By using a factorial experiment within RCBD with three replications, the results revealed that indicated to significant differences in the response of four varieties under the effect of the Nitrogen fertilization levels in both locations in the criteria concerned with sweetness such as TS%,TSS%, and NSS%, while the significant effect of Nitrogen levels N2 and N3 were revealed in quality related criteria TS% and TSS% in both locations.